COACHING LEADERSHIP EXERCISED BY NURSES IN THE HOSPITAL SETTING - Karen Yukari Hayashida; Andrea Bernardes; André Almeida de Moura; Carmen Silvia Gabriel; Alexandre Pazetto Balsanelli (Universidade Federal do Paraná, 2019)
Objective: To identify and compare the self-perception of nurses and the perception of nursing aides and nursing technicians towards coaching leadership practices. Method: This was a cross-sectional study carried out in 2016 with 69 nurses and 233 nursing aides and technicians from two public hospitals in the Brazilian state of São Paulo. The researchers administered two validated questionnaires about the exercise of this type of leadership by nurses, addressing the self-perception of nurses and the perception of nursing aides and nursing technicians. Results: Of the four dimensions of coaching leadership, communication was the most recognized. In hospital A, the perceptions of professionals from both categories regarding the practice of leadership exercised by nurses were similar. In hospital B, the self-perception of nurses regarding the exercise of coaching leadership was higher than the perception of nursing aides and nursing technicians, except for the communication dimension. Conclusion: coaching leadership and its dimensions can benefit institutions and nursing professionals by helping improve team management.